Contemporary influences of C.G. Jung's thought - Błocian, Ilona; Kuzmicki, Andrew (Contemporary psychoanalytic studies, 2018)
The book is a volume of the collected works of sixteen different authors. They reflect the contemporary meaning of C.G. Jung's theory on many fields of scientific activity and in a different cultural context: Japanese, South American and North American, as well as European: English, Italian and Polish. The authors consider a specific milieu of Jung's theory and his influence or possible dialogue with contemporary ideas and scientific activity. A major task of the book will be to outline the contemporary-direct or indirect-usefulness and applicability of Jung's ideas at the beginning of the twenty-first century while simultaneously making a critical review of this theory.